2004
DOI: 10.1097/00007611-200405000-00022
|View full text |Cite
|
Sign up to set email alerts
|

Female Genital Schistosomiasis: Case Report and Review of the Literature

Abstract: A 37-year-old woman, originally from South Africa, presented for a gynecologic examination. Speculum examination revealed a friable cervical lesion. Both the cervical smear and biopsy contained intact, viable schistosome eggs consistent with those of Schistosoma haematobium. Appropriate treatment was initiated promptly, avoiding significant morbidity. The diagnosis of female genital schistosomiasis must be considered when the patient has a history of travel to or residence in endemic areas.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
24
0

Year Published

2007
2007
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 21 publications
(24 citation statements)
references
References 12 publications
0
24
0
Order By: Relevance
“…A Spanish study by Roca et al (16) found 200 cases (15.2%) of schistosomiasis among 1321 African immigrants, almost 50% of whom were asymptomatic and 30% had nonspecific abdominal pain. Female genital schistosomiasis is a frequent complication in women with urinary or systemic schistosomiasis, and it may go undiagnosed in nonendemic countries where physicians are unlikely to be familiar with this syndrome (17).…”
mentioning
confidence: 99%
“…A Spanish study by Roca et al (16) found 200 cases (15.2%) of schistosomiasis among 1321 African immigrants, almost 50% of whom were asymptomatic and 30% had nonspecific abdominal pain. Female genital schistosomiasis is a frequent complication in women with urinary or systemic schistosomiasis, and it may go undiagnosed in nonendemic countries where physicians are unlikely to be familiar with this syndrome (17).…”
mentioning
confidence: 99%
“…However, with increased numbers of immigrants from and tourists to endemic areas, several female genital schistosomiasis cases have been reported in this country. [2][3][4][5] Furthermore, the actual number of female genital schistosomiasis cases in the United States potentially could be higher for the following reasons: schistosomiasis is not a reportable disease, female genital schistosomiasis can be asymptomatic for a long time after exposure, and the worm can live for up to 30 years. Here we report a case of cervical schistosomiasis due to S hematobium in a healthy, asymptomatic African immigrant in New England.…”
Section: Discussionmentioning
confidence: 99%
“…Three major species of schistosomes are described: S. haematobium , S. japonicum , and S. mansoni [4]. S. haematobium infection is acquired predominantly in North Africa, sub-Saharan Africa, the Middle East, Turkey, and India.…”
Section: Discussionmentioning
confidence: 99%
“…No other symptom is reported. S. haematobium is the organism most often identified in FGS [1, 4, 6]. In most cases, the lesions are found on the labia majora [6].…”
Section: Discussionmentioning
confidence: 99%